2016
DOI: 10.3835/plantgenome2015.09.0082
|View full text |Cite
|
Sign up to set email alerts
|

AP2/ERF Transcription Factors Involved in Response to Tomato Yellow Leaf Curly Virus in Tomato

Abstract: Tomato yellow leaf curly virus (TYLCV), transmitted by the whitefly (Bemisia tabaci), causes leaf curling and yellowing, plant dwarfism, and growth inhibition in tomato (Solanum lycopersicum L.). The APETALA2 (AP2) and ethylene response factor (ERF) transcription factor (TF) family, the largest plant-specific TF family, was identified to function in plant development and pathogen defense. Our study aimed to analyze the mechanism underlying the function of S. lycopersicum ERF (SlERF) TFs in response to TYLCV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 84 publications
(79 reference statements)
1
34
0
Order By: Relevance
“…Orthologous genes of SolyWRKY80, SolyWRKY81, SolyWRKY53, and SolyWRKY54, AtWRKY53 (At4g23810) and AtWRKY70 (At3g56400) were important in plant-pathogen interaction [ 19 ]. In addition to WRKY TFs, AP2/ERF TFs could respond to TYLCV infection, and 5 different SolyERF genes ( Soly19 , Soly36 , Soly106 , Soly67 , and Soly66 ) are involved in TYLCV defense with a complex network through positive and negative expression [ 77 ]. Negative and positive regulations were both important for gene expression [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Orthologous genes of SolyWRKY80, SolyWRKY81, SolyWRKY53, and SolyWRKY54, AtWRKY53 (At4g23810) and AtWRKY70 (At3g56400) were important in plant-pathogen interaction [ 19 ]. In addition to WRKY TFs, AP2/ERF TFs could respond to TYLCV infection, and 5 different SolyERF genes ( Soly19 , Soly36 , Soly106 , Soly67 , and Soly66 ) are involved in TYLCV defense with a complex network through positive and negative expression [ 77 ]. Negative and positive regulations were both important for gene expression [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Function and Expression Pattern of AP2/ERF TFs under Biotic Stresses AP2/ERF TFs were associated with the regulation of disease resistance in plants. Overexpression of TaPIE1 [157], OsEREBP1 [158], Soly106 [159], GmERF113 [160] and OsERF83 [161] genes, in response to JA, SA or ET mediated signal transduction pathways, were believed to be effective against pathogen infection. HvRAF, a novel AP2/ERF TF in barley, had dual regulatory functions under biotic (R. solanacearum) and abiotic (salinity) stresses [162].…”
Section: Function and Expression Pattern Of Ap2/erf Tfs Under Abioticmentioning
confidence: 99%
“…In Arabidopsis thaliana, an AP2/ERF transcription factor (MACD1), was found to be involved in phytotoxin-triggered programmed cell death [44]. Huang, et al [45] reported that AP2/ERF transcription factors were reported to interact with the MAPK, and jasmonic acid, salicylic acid, ethene, and H 2 O 2 pathways to improve the ability of tomato plants to respond to yellow leaf curly virus. GPX is a redox sensor protein that maintains a steady-state of H 2 O 2 in plant cells and has a pivotal role in peroxide detoxification in eukaryotic organisms [46].…”
Section: Genes Involved In Plant Defense and Related Signal Pathwaysmentioning
confidence: 99%